2013
DOI: 10.3390/rs5094470
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Coastline in Aquaculture Coast from Multispectral Remote Sensing Images: Object-Based Region Growing Integrating Edge Detection

Abstract: Aquaculture coasts have become widely distributed in coastal zones as human activities are intensified. Due to the complexity in this type of coast, it is difficult to extract the coastline with traditional automated mapping approaches. In this paper, we present an automated method-object-based region growing integrating edge detection (OBRGIE) for the extraction of this type of coastline. In this method, a new object feature named OMI (object merging index) is proposed to separate land and sea. The OBRGIE met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 31 publications
1
56
0
2
Order By: Relevance
“…Most studies on Landsat land cover classification have reported the superior performance of OBIA in various landscapes such as urban areas [89,156], agricultural areas [79,85], forests [86,128] and wetlands [47,157]. The major advantage of OBIA is that it represents the classification units as real world objects on the ground and hence reduces the within class variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on Landsat land cover classification have reported the superior performance of OBIA in various landscapes such as urban areas [89,156], agricultural areas [79,85], forests [86,128] and wetlands [47,157]. The major advantage of OBIA is that it represents the classification units as real world objects on the ground and hence reduces the within class variability.…”
Section: Discussionmentioning
confidence: 99%
“…While pixel and sub-pixel based approaches were commonly developed and applied on Landsat images, OBIA classification was developed at a time when finer resolution images were available. Therefore, this method has been commonly applied on finer resolution imagery than Landsat images [9,19,47]. …”
Section: Developments Of Computer-based Land Cover Classification Metmentioning
confidence: 99%
“…The Digital Shoreline Analysis System (DSAS) [68], a free extent for ArcGIS software, was applied in this study to determine the degree of position differences between extracted coastlines [69], such as NSM and AD. NSM represents a distance between the reference and the extracted coastline at each transect.…”
Section: Validation Of Coastline Extractionmentioning
confidence: 99%
“…To date, various remotely sensed data have been widely used for mapping and detecting changes in coastal zones because of their relatively low cost compared with traditional approaches [13][14][15][16][17]. In this study, Landsat imagery with a 30-m spatial and 16-d temporal resolution was selected as the main data source for tracking the temporal change of estuarine islands [18].…”
Section: Introductionmentioning
confidence: 99%